Markets on a (Computer) Chip? New Perspectives on Economic Calculation. - Jablonowski, Mark (Science & Society, 2011)
Is it possible to implement an efficient economic alternative to market capitalism using economic planning? The debate, which has blown both hot and cold over the last 80 years, has turned on the feasibility of calculating solutions to what amounts to a vast quantity of economic equations. More recently, issues of respecting the uncertainty and preserving the information content inherent in “real world” economic transactions have surfaced. The question may ultimately be decided not on how much computing power is needed to solve complex economic problems, but rather on how well new solutions are articulated. New developments in computer “chip level” computation, including the rebirth of electronic analogs and the incorporation of the fuzzy set formalism for computing in complex systems, may impart a greater feasibility to the idea of deliberate public planning that integrates the benefits of the market process for the achievement of social objectives. These developments have implications for establishing workable alternatives to capitalism. Reprinted by permission of the publisher.